Minimally invasive laminar lift and posterior cervical laminoplasty via the intermuscular approach: a canine model study - Yan,Fei (2022)
ABSTRACT Purpose: This study aimed to develop a minimally invasive surgical procedure for laminar lift and posterior cervical laminoplasty via the intermuscular approach using a canine model. Methods: Six Alaskan dogs were used for developing the surgical approach. The bilateral laminae of C3-7 were cut with an ultrasonic osteotome and fixed with bilateral plates to maintain the lamina lifting and reshape a wider spinal canal. The important structures, such as ligaments, supraspinous ligaments, interspinous ligaments, and ligamentum flavum were preserved. The therapeutic effect was evaluated by preoperative and postoperative imaging results and neck mobility. Results: The surgical procedures were all successfully performed in the 6 animals. All the dogs survived well within 1 year of postoperative follow-up. The postoperative neck mobility was as good as the preoperative one. Computed tomography results showed that the anteroposterior diameter of the spinal canal was successfully enlarged and maintained well. Conclusions: The minimally invasive surgical procedure for laminar lift and posterior cervical laminoplasty via the intermuscular approach was feasible in a canine model, which might be applied in clinical practice.